Jesus, Paul, and early Christianity : studies in honour of Henk Jan de Jonge - Buitenwerf, Rieuwerd.; Hollander, Harm W.; Jonge, H. J. de.; Tromp, Johannes. (Novum Testamentum, Supplements, 2008)
This collection of essays by leading experts in New Testament scholarship addresses core themes in the study of early Christianity. The topics addressed include text-critical issues relating to the New Testament, the historical situation in which the earliest Christian documents were composed, early Christian rituals, historical questions concerning Jesus and Paul, and the origin and development of important theological ideas in the early Church. This volume is dedicated to Henk Jan de Jonge (Emeritus Professor in the New Testament, Leiden University) in honour of his important contributions to the field of New Testament Studies.